Women's Involvement in Politics According to Islamic Law - Febri Sahrul Romadon (Sahabat Publikasi, 2026)
The development of new media, particularly social media, has brought significant changes to modern human life, including in the political sphere. Social media serves not only as a means of communication but also as a strategic platform for women to enhance their political participation. In Indonesia, women's political rights have been guaranteed through various conventions and regulations; however, women's representation in political institutions continues to face structural, cultural, and historical obstacles. Women’s political participation is essential to the decision-making process, both directly and indirectly, as gender bias in public policy remains prevalent. From an Islamic perspective, women's political participation has a strong foundation, although scholars differ regarding the limits of such involvement. This study examines the evolution of women's political participation, its inhibiting factors, and the Islamic legal arguments concerning women's involvement in politics. The findings indicate that increasing women's political participation requires affirmative policy support, the dissemination of political education, and the use of social media as an effective empowerment tool.